Antioxidant, anti-tyrosinase and anti-inflammatory activities of 3,5-dihydroxy-4′,7-dimethoxyflavone isolated from the leaves of Alpinia nigra - Gupta M.K.; Senthilkumar S.; Chiranjivi A.K.; Banik K.; Girisa S.; Kunnumakkara A.B.; Dubey V.K.; Rangan L. (My University, 2025)
Background: Overexposure to sunlight and high UV radiation leads to uncontrolled melanin production in the skin, leading to hyperpigmentation and inflammatory diseases. Therefore, there is a need to discover safe and highly prospective drugs from natural sources. Previous studies have shown that leaves and rhizome extract of Alpinia nigra possesses antioxidant and anti-inflammatory activities. Among the components of the most bioactive methanol and ethyl acetate extract, flavones seem to be the most promising compound. Aim: To evaluate the antioxidant, anti-tyrosinase and anti-inflammatory efficacy of 3,5-dihydroxy-4′,7-dimethoxyflavone (DHDM). Methods: The flavone DHDM was isolated from A. nigra ethyl acetate leaf extract and characterized by multi spectroscopic techniques. The toxicity of DHDM was evaluated by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. The antioxidant and reactive oxygen species (ROS) inhibitory activity were determined by 2,2-Diphenyl-1-picrylhydrazy (DPPH) assay and by flow cytometry. Further, the anti-tyrosinase activity was evaluated by in silico (molecular docking), fluorescence, and enzyme kinetics studies. The anti-inflammatory activity was demonstrated by western blotting. Results: The cell viability assay with DHDM showed no inhibition at ≤200 µM concentration in THP-1 (human macrophage) and ≤80 µM in HaCaT (human keratinocyte) cell lines. Additionally, strong antioxidant properties and reduced ROS generation suggested prevention from oxidative damage and skin aging. Strong binding of DHDM to tyrosinase leading to the conformational change was revealed by fluorescence quenching studies and molecular docking. Further, the anti-tyrosinase activity of the isolated compound was observed at 42.5 µM (IC50). Moreover, DHDM inhibited the expression of anti-inflammatory proteins like TNF-α and NF-κB. Conclusion: The DHDM demonstrates the efficient antioxidant, anti-tyrosinase and anti-inflammatory potential, which could be developed for obtaining a new drug for the management of hyperpigmentation and inflammatory-related diseases. © 2021